Role of ATG7-dependent non-autophagic pathway in angiogenesis - Chen, Jinxiang; Liang, Yu; Hu, Shaorun; Jiang, Jun; Zeng, Min; Luo, Mao (Frontiers in Pharmacology, 2024)
ATG7, one of the core proteins of autophagy, plays an important role in various biological processes, including the regulation of autophagy. While clear that autophagy drives angiogenesis, the role of ATG7 in angiogenesis remains less defined. Several studies have linked ATG7 with angiogenesis, which has long been underappreciated.The knockdown of ATG7 gene in cerebrovascular development leads to angiogenesis defects. In addition, specific knockout of ATG7 in endothelial cells results in abnormal development of neovascularization. Notably, the autophagy pathway is not necessary for ATG7 regulation of angiogenesis, while the ATG7-dependent non-autophagic pathway plays a critical role in the regulation of neovascularization. In order to gain a better understanding of the non-autophagic pathway-mediated biological functions of the autophagy-associated protein ATG7 and to bring attention to this expanding but understudied research area, this article reviews recent developments in the ATG7dependent non-autophagic pathways regulating angiogenesis.